Atualização da rede GPS de São Carlos e a avaliação do método "PPP" em comparação com o ajustamento de redes geodésicas - Pereira, Luiz Antonio (2007)
Atulim (2002) and Racanicchi (2003) had planned and implemented a geodetic GPS network in São Carlos city, which needed maintenance and revision. The proposals of this dissertation had consisted of: i) to bring up to date the GPS geodetic network in the city of São Carlos and to make it compatible with the SIRGAS2000 (Geocentric Reference System of Americas 2000), with new network adjustment and injunction in two geodesic vertices in the urban area of São Carlos, homologated by the IBGE after the implantation of the original geodetic network in 2003; ii) to evaluate and to compare the new results of the geodetic network coordinates obtained with the relative positioning through the tracking of artificial satellites, according to technology NAVSTAR/GPS and adjusted through the Least Squares Method, with results of coordinates obtained through the Precise Point Positioning (PPP) Method, processed by PPP on-line services. Analyzing the results obtained in this dissertation, it was possible to evaluate that the application of PPP Method, since that followed the specific orientations of each on-line service used, takes care perfectly to the required to support of cadastral registry and location services for the most varied purposes, however it does not substitute yet other services that demand highest degree of accuracy only obtained with vectors and network adjustment with statistical control of processes that demand high computational activity.